Pharmacogenomics Education and Knowledge Assessment in Healthcare Curricula: A Scoping Review of the Middle East and North Africa Region - Asmaa Ibrahim; Reem Alenany; Loulia Bader; Fatima Nazar; Sara Abulola; Ola Almasalmeh; Sadaf Riaz; Hilyatuz Zahroh; Fatima Mraiche (Pharmacology Research & Perspectives)
ABSTRACT Pharmacogenomics (PGx) is a crucial part of precision medicine; however, its integration into clinical practice has been slow, primarily due to knowledge gaps regarding pharmacogenomics among healthcare professionals (HCPs). Pharmacogenomics education is considered the most influential barrier to the successful implementation of PGx. In the Middle East and North Africa (MENA) region, several studies have highlighted the lack of PGx education among students and HCPs. This scoping review aims to provide an overview of the existing literature on how PGx is delivered in the curricula and its impact on knowledge acquisition among students and HCPs in the MENA region. A database search of PubMed, Embase, and CINAHL was conducted up to June 2023. Outcomes included PGx education availability, curriculum placement, mode of delivery, and knowledge level. Seven cross‐sectional studies were identified (2014–2023), with 57% from the Gulf region. PGx education is mostly taught to undergraduates (71%) through didactic lectures (100%), with only a few studies reporting a standalone course (29%). Participants demonstrated low (43%) to moderate (43%) knowledge levels, assessed using objective scales or subjective self‐assessment after completion of the course. Reported barriers to implementing PGx education included knowledge gaps, economic constraints, and system sustainability. PGx education in the MENA region is delivered mainly as an integrated course in professional programs including pharmacy and medicine, and the overall knowledge level was low to moderate. Future research could focus on providing more detailed reporting of the PGx educational landscape, developing standardized assessment tools, and evaluating actual knowledge acquisition among different professions.